THE EFFECT OF PRICE AND ADVERTISING ON BRAND SWITCHING SCOOTER MOTORCYCLE IN MANADO - Pantow, Erick F. (Universitas Sam Ratulangi, 2019)
Abstract: Consumer brand switching behavior on scooter motorcycle product is reflects the shift from a product brand commonly consumed with other brand products. It is important to any companies to anticipate any changes in its customers’ preferences, especially all variables related to the price and advertising. This study is to know the effect of price and advertising on brand switching scooter motorcycle in Manado. The type of this research is quantitative research method and the population is the people in Manado who have experience in switching of scooter motorcycle brand. The sampling technique in this study used convenience sampling method. Based on data result concluded that: price has significant effect on brand switching scooter motorcycle and advertising has significant effect on brand switching scooter motorcycle in Manado. if the price is higher, then the decision to switch brand will increase and if the competitor’s advertisement is increasingly attractive, then the decision to switch brand will increase. The company should be considering an affordable price for each new product that will be release with a nice, proper, and fresh advertisement, that not only shows how great the product is, but focusing on how it can affect and fulfill the customer needs.Keyword: brand Switching, price, advertising